Psychosis and Hopelessness Mediate the Relationship Between Reduced Sleep and Suicidal Ideation in Schizophrenia Spectrum Disorders. Issue 4 (2nd October 2022) - Carruthers, Sean P.; Lee, Stuart J.; Sankaranarayanan, Anoop; Sumner, Philip J.; Toh, Wei Lin; Tan, Eric J.; Neill, Erica; Van Rheenen, Tamsyn E.; Gurvich, Caroline; Rossell, Susan L.
Abstract: Objective: Suicide is a major cause of death amongst individuals with schizophrenia spectrum disorders (SSD). Despite numerous risk factors being identified, accurate prediction of suicidality and provision of tailored and effective treatment is difficult. One factor that may warrant particular attention as a contributor to increased psychopathology and suicidality in SSD is disturbed sleep. Sleep disturbances have been reliably linked to greater levels of suicidal ideation and are highly prevalent amongst individuals with SSD. This study aimed to examine if reduced sleep duration and psychopathology are associated with increased suicidal ideation. Method: One-hundred and eighteen adults with chronic SSD living within the community participated in this cross-sectional study. Psychosis symptoms were assessed using the Positive and Negative Syndrome Scale. Items 4 and 10 from the Montgomery-Asperg Depression Rating Scale and Item 2 from the Calgary Depression Scale for Schizophrenia were used to assess reduced sleep duration, current suicidal ideation, and hopelessness, respectively. All measures were rated concurrently. Results: A hierarchical logistic regression revealed that greater acute sleep disturbances were associated with increased suicidal ideation and this relationship was found to be uniquely mediated by both positive symptom severity and hopelessness. Conclusion: These results suggest that individuals with SSD who exhibited disrupted or disordered sleep, positive symptoms and/or hopelessness should be routinely screened for suicidal thinking. Furthermore, interventions that effectively target sleep disruptions may provide much-needed action against suicidal ideation. HIGHLIGHTS: Reduced sleep found to be associated with increased suicidal ideation This was uniquely mediated by both hopelessness and positive symptoms More regular screening of sleep problems in schizophrenia is needed